Relações entre Estação Ecológica do Taim e comunidade local: conflitos e cooperação - Sete, Lucas Rogerio (2010)
The creation of protected areas is one of the main historical claims of conservation of the nature movements and also one of the main strategies adopted by the governments and environmental entities for the conservation of the environment and of their natural resources. The responsible organs for the creation and administration of the units of conservation as the ecological stations, have employed authoritarian and technocratic political, that result in conflicts with the local communities, with prominence for the expropriation of the lands; dispute of waters; restrictions to the hunt and fishing; among other, with so much damage to the conservation ends as of development of the populations of the spill (especially traditional groups). Front to this scenery compatible forms have been looked between the conservation objectives and development by diverse strategies, with emphasis in the valorization of the vision and participation of the local populations in the actions and decisions of the administration. The researches about perception of local community offer instruments for the understanding of behaviors and they aid in the improvement of the process of environmental administration. This work approaches the problem of the harmonization between conservation objectives and development in the case of the Ecological Station of Taim that is constituted in an area of integral protection that, in his implantation, it implicated the removal of some families and introduction of new restrictive norms for the populations that live in yours spill. In that context intends to observe the conflicts that appeared with the new scenery, and the conciliation initiatives among the conservation purposes and development that it has been accomplished in the area. The data of this qualitative research were obtained in the period of January from 2009 to January of 2010, with the technique of the semistructured interview, combined with secondary data, bibliographical consultations and observations in the place. The lifted up data indicate that the population notices the existence of several embarrassments in the conservationist speech and divergences among the purposes of the unit of conservation and of the resident population in the spill. The initiatives of harmonization of the conservation purposes and development are several, but still incipient and dependent of external resources, what restricts their impacts.